Bike and run pacing on downhill segments predict Ironman triathlon relative success - Johnson, E. C.; Pryor, J. L.; Casa, D. J.; Belval, L. N.; Vance, J. S.; DeMartini, J. K.; Maresh, C. M.; Armstrong, L. E. (Journal of Science and Medicine in Sport, 2015)
Objectives: Determine if performance and physiological based pacing characteristics over the varied terrain of a triathlon predicted relative bike, run, and/or overall success. Poor self-regulation of intensity during long distance (Full Iron) triathlon can manifest in adverse discontinuities in performance. Design: Observational study of a random sample of Ironman World Championship athletes. High performing and low performing groups were established upon race completion. Methods: Participants wore global positioning system and heart rate enabled watches during the race. Percentage difference from pre-race disclosed goal pace (%off) and mean HR were calculated for nine segments of the bike and 11 segments of the run. Normalized graded running pace (accounting for changes in elevation) was computed via analysis software. Step-wise regression analyses identified segments predictive of relative success and HP and LP were compared at these segments to confirm importance. Results: %Off of goal velocity during two downhill segments of the bike (HP: -6.8 ± 3.2%, -14.2 ± 2.6% versus LP: -1.2 ± 4.2%, -5.1 ± 11.5%; p < 0.020) and %off from NGP during one downhill segment of the run (HP: 4.8 ± 5.2% versus LP: 33.3 ± 38.7%; p = 0.033) significantly predicted relative performance. Also, HP displayed more consistency in mean HR (141 ± 12 to 138 ± 11 bpm) compared to LP (139 ± 17 to 131 ± 16 bpm; p = 0.019) over the climb and descent from the turn-around point during the bike component. Conclusions: Athletes who maintained faster relative speeds on downhill segments, and who had smaller changes in HR between consecutive up and downhill segments were more successful relative to their goal times.